1988
DOI: 10.1111/j.1365-3091.1988.tb00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Sand waves, Echinocardium traces and their bathyal depositional setting (Monte Torre Palaeostrait, Plio‐Pleistocene, southern Italy).

Abstract: Stacked cross‐sets, up to 2.5 m thick, produced by sand wave migration and meniscate trace fossils produced by Echinocardium cordatum, both considered in the literature as typical of shallow‐water marine depositional settings, commonly occur in the bathyal Plio‐Pleistocene deposits of Monte Torre (Calabria, southern Italy). The Plio‐Pleistocene sediments form two coarsening‐upward depositional sequences, separated by an unconformity and by a palaeobathymetric gap of at least 300 m. The lower sequence passes up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…60 years) interbedded with sandwave deposits and derived from the rugged and tectonically unstable basin margins. The Monte Torre paleostrait of southern Italy – which linked the Tyrrhenian and Ionian seas during Plio‐Pleistocene time (Colella & D'Alessandro, 1988) – provides a well‐documented fossil analogue of the Messina Strait. Sedimentation along the axis of the paleostrait was characterized by gravel or very coarse sandwave deposits composed mostly of carbonate biodetritus.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…60 years) interbedded with sandwave deposits and derived from the rugged and tectonically unstable basin margins. The Monte Torre paleostrait of southern Italy – which linked the Tyrrhenian and Ionian seas during Plio‐Pleistocene time (Colella & D'Alessandro, 1988) – provides a well‐documented fossil analogue of the Messina Strait. Sedimentation along the axis of the paleostrait was characterized by gravel or very coarse sandwave deposits composed mostly of carbonate biodetritus.…”
Section: Discussionmentioning
confidence: 66%
“…The Monte Torre sandwave deposits are interbedded with thick turbidites – the result of intermittent high‐density turbidity currents mobilizing mixed bioclastic–siliciclastic detritus from the tectonically active basin margins. Based on ichnofacies, stratigraphic relationships and sedimentary facies analyses, Colella & D'Alessandro (1988) concluded that deposition in the Monte Torre paleostrait occurred at water depths in excess of 350 m.…”
Section: Discussionmentioning
confidence: 99%
“…2001; Cucci 2004); the Catanzaro palaeoisthmus, which repeatedly separated Central Calabria from the Serre massif until the Late Pleistocene (Ghisetti 1979; Caloi et al. 1989); the Monte Torre basin which was open approximately until the uppermost Early Pleistocene (Colella & D’alessandro 1988; Bonfiglio et al. 2002) and separated the Serre and the Aspromonte massifs; and finally the Crati river valley (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…b). These seaways were filled by 80‐ to 200‐m‐thick deepening‐upward successions during dramatic phases of tectonic‐driven marine transgressions (Colella and D'Alessandro, ; Longhitano and Nemec, ; Longhitano et al ., ). Tidal currents were amplified flowing in phase opposition from one basin to the other, like the modern Messina Strait (Figs.…”
Section: Dataset Of Ancient Examplesmentioning
confidence: 99%